Fabry Disease: Symptoms in Children and Teenagers - L. М. Kuzenkova; L. S. Namazova-Baranova; Т. V. Podkletnova; А. K. Gevorkyan; N. D. Vashakmadze; K. V. Savostyanov; V. М. Studenikin; S. А. Pushkov ("Paediatrician" Publishers LLC, 2015)
Fabry disease is a serious degenerative hereditary disorder, which is referred to as a lysosomal storage disease and is a form of sphingolipidosis. Fabry disease often starts in childhood and adolescence, although the complete clinical manifestation occurs in adulthood. Early diagnostic is often difficult due to polymorphic clinical picture, untypical initial symptoms and doctors' low level of awareness. Fabry disease patients should undergo a special kind of pathogenetic enzyme replacement therapy. Timely diagnosis and prompt treatment can prolong life expectancy and improve life quality.